(3ecGJHI QeR Edi CHj JQGHs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hUdJ ecGJHI GdTjhN CNhJi CWGd Gddg HbGge hCOGe Jhajbge hYdGge hhbaJ Ydi eVehfgG s
(3BNQgG (B:s
(3hTjhN GdHSJGf hcPdc ef HGdMVQI hLejY ef HGdNUU HCJe GdJMjI hGdMeO ddg QH GdYGdejf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B107s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds